Uranium Deposits of Canada - Robertson, David; Lattanzi, C. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1974)
Summary World demand for uranium is expected to increase at an average rate of about 15 per cent per year over the next 20 years. This is a rate of increase not previously faced by any mineral commodity. Descriptions of Canada's uranium ore bodies and consideration of modes of origin, suggest environments in which new ore bodies can be found and indicate some of the geological problems to be considered in uranium search. Canada, which has been a prominent supplier of uranium to meet the world's needs in the past, will continue to be a major source of this commodity.